Given: The following Boolean expressions where x is assumed to be 1: (true) && (3 > 4) !(x > 0) && (x > 0) (x > 0) || (x < 0) (x != 0) || (x == 0) (x >= 0) || (x < 0) (x != 1) == !(x == 1) T o find: The result of the Boolean expressions when x is 1: (true) && (3 > 4) !(x > 0) && (x > 0) (x > 0) || (x < 0) (x != 0) || (x == 0) (x >= 0) || (x < 0) (x != 1) == !(x = =1) Solution: The expression (true) && (3 > 4) evaluates to false. In && operator, both the operands should be true. 3 > 4 is false. true && false gives false. Therefore, the result of this expression is false. The expression or statement !(x > 0) && (x > 0) evaluates to false. x > 0 is true, which makes !(x > 0) false. false && true gives false...
Given: The following Boolean expressions where x is assumed to be 1: (true) && (3 > 4) !(x > 0) && (x > 0) (x > 0) || (x < 0) (x != 0) || (x == 0) (x >= 0) || (x < 0) (x != 1) == !(x == 1) T o find: The result of the Boolean expressions when x is 1: (true) && (3 > 4) !(x > 0) && (x > 0) (x > 0) || (x < 0) (x != 0) || (x == 0) (x >= 0) || (x < 0) (x != 1) == !(x = =1) Solution: The expression (true) && (3 > 4) evaluates to false. In && operator, both the operands should be true. 3 > 4 is false. true && false gives false. Therefore, the result of this expression is false. The expression or statement !(x > 0) && (x > 0) evaluates to false. x > 0 is true, which makes !(x > 0) false. false && true gives false...
Solution Summary: The author analyzes the Boolean expressions when x is assumed to be 1: (true) && (3 > 4) evaluates to false.